(untitled) (Research, Society and Development, 2021)
Vegetables play an important role in human nutrition, due to their nutritional value, being rich in various vitamins and minerals. The main vegetables produced in Brazil today are lettuce, potatoes, carrots, onions and tomatoes. The objective of this work was to present the current demand scenario for vegetable seeds, as well as to address the main factors that can contribute, both positively and negatively, to the future of seed production in Brazil. The current scenario is one of reduced demand for lettuce, carrot and tomato seeds, due to the economic problems caused by the pandemic, and maintenance in relation to potato and onion crops. The perspective for the increase in demand for vegetable seeds is linked to the duration of the pandemic and economic stabilization in the country. Population growth and the UN campaign that reports the importance of vegetables for the health of the population are factors that can increase the demand for vegetable seeds.